PENGGUNAAN ARBITRASE NASIONAL SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA ASURANSI UMUM - Reynaldo Murat; Yanti Fristikawati (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2021)
Insurance is a coverage where a party act as the Insurer while the other party act as the Insured and proven by the agreement which is called by the Policy. Since 2011, insurance industry was being supervised by the Indonesia Financial Services Authority (OJK). Therefore, in carrying out its business activities should comply with the OJK regulations, including to determine the dispute clause in the Policy. The Alternative Dispute Resolutions for the Financial Services Sector has been established by OJK at the end of 2020 which provide an opportunity to the disputing party to solve their dispute outside the court. Indonesia has BANI Arbitration Center (BANI) which could be used as an alternative forum to settle the general insurance disputes in Indonesia, however it is contrary with regulation which has been issued by the OJK.